2012
DOI: 10.1302/0301-620x.94b11.29601
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of high tibial osteotomy in the treatment of osteoarthritis of the knee

Abstract: Previous studies from single centres or single-surgeon series report good early and midterm results for high tibial osteotomy (HTO) in the treatment of osteoarthritis of the knee. However, the survivorship of HTO at a national level is unknown. This registry-based study included 3195 high HTOs performed between 1987 and 2008. Kaplan-Meier analysis revealed an overall survivorship of 89% (95% confidence interval (CI) 88 to 90) at five years and 73% (95% CI 72 to 75) at ten years, when conversion to total knee r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
82
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 18 publications
9
82
0
4
Order By: Relevance
“…The present study is a single-centre study resulting in relatively few patients left to evaluate after 10 years. One-third of the patients included in our study had been converted to knee arthroplasty within 10 years and that is in line with the findings in earlier published population-based studies from Sweden [25] and Finland [10], showing that the 10-year risk of revision was approximately 30 %. However, there are some publications including at least 100 patients, showing rates of revision at 10 years between 5 and 20 % [4-6, 12, 22].…”
Section: Discussionsupporting
confidence: 91%
“…The present study is a single-centre study resulting in relatively few patients left to evaluate after 10 years. One-third of the patients included in our study had been converted to knee arthroplasty within 10 years and that is in line with the findings in earlier published population-based studies from Sweden [25] and Finland [10], showing that the 10-year risk of revision was approximately 30 %. However, there are some publications including at least 100 patients, showing rates of revision at 10 years between 5 and 20 % [4-6, 12, 22].…”
Section: Discussionsupporting
confidence: 91%
“…This survivorship number is consistent with numbers reported by other authors. [47][48][49][50][51][52] As expected, the need for arthroplasty was associated with longer follow-up periods. 37 Surprisingly, osteotomy fixation with a smaller plate with only 4 screws was associated with increased postoperative pain even after correction for follow-up length (the senior author predominantly used the smaller plate early in the study).…”
Section: Discussionsupporting
confidence: 66%
“…Longterm results theoretically should not be worse than currently published results of standard HTO cases, whereby it has been reported that the survivorship of osteotomy ranges from 75% to 95% up to 5 years and from 51% to 98% at 10 years. [53][54][55][56][57][58][59][60][61] The trial design for a phase II randomized controlled trial using the described technique has just been approved by the US Food and Drug Administration involving the institutions of the first and second authors (K-Y.S. and A.A.), the first author being the principal investigator.…”
Section: High Tibial Osteotomy and Chondrogenesismentioning
confidence: 99%